2015
DOI: 10.4172/2472-128x.1000125
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenomic Delineation and Clinical Characterization of Three Cases of MECP2 Duplication Syndrome

Abstract: The methyl-CpG-binding protein 2 gene (MECP2) on the X chromosome encodes an essential epigenetic regulator in human postnatal brain development. Increased dosage of MECP2 causes a severe syndromic form of intellectual disability, the MECP2 duplication syndrome. Males with this syndrome have a progressive neurological disorder, severe to profound intellectual disability, epilepsy and recurrent respiratory infections. We report three cases with copy number gain in Xq28 involving the MECP2 gene. The gains were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…A few reports commented on the use of adjuvant therapy, such as vagus nerve stimulation, deep brain stimulation, ketogenic diet, or corpus callosotomy. 6,9,21,25,27 In our study, parents reported an improvement in seizure frequency and severity in 4/5 patients treated with vagus nerve stimulation and in 5/7 children treated with the ketogenic diet. However, larger collaborative studies are needed for a truly objective assessment of therapeutic efficacies.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…A few reports commented on the use of adjuvant therapy, such as vagus nerve stimulation, deep brain stimulation, ketogenic diet, or corpus callosotomy. 6,9,21,25,27 In our study, parents reported an improvement in seizure frequency and severity in 4/5 patients treated with vagus nerve stimulation and in 5/7 children treated with the ketogenic diet. However, larger collaborative studies are needed for a truly objective assessment of therapeutic efficacies.…”
Section: Discussionsupporting
confidence: 55%
“…This finding is in contrast to the estimated 10% EE frequency in the published cases (table e-1). [3][4][5][6][7]9,10,[17][18][19][20][21][22][23][24][25] There are several possible reasons underlying the differences in the frequency of epilepsy and EE observed in our case series and that estimated from review of published cases summarized in table e-1. (1) Ascertainment bias-the epileptic phenotype was scrutinized systematically and in detail in this study while published case reports and case series differ in their focus and depth of investigation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Neonatal complications include early infantile hypotonia (388 of 441 individuals from 62 studies [ 1 , 3 , 4 , 7 , 9 27 , 29 34 , 36 , 38 , 41 43 , 46 48 , 51 53 , 55 , 59 61 , 63 , 64 , 67 , 69 71 , 73 78 , 81 86 ]), feeding difficulties with poor sucking [ 16 , 73 , 77 ], bowel obstruction [ 17 , 74 ], malaise and vomiting [ 77 ], respiratory distress [ 77 ], breathing problems [ 84 ], hospitalisation for infections [ 77 , 84 ] and failure to thrive [ 1 , 9 , 12 , 13 , 16 , 17 , 22 , 25 , 27 , 29 , 32 , 38 , 43 , 44 , 51 , 61 , 64 , 67 , 81 , 82 ]. Developmental/psychomotor delay has been reported in most (n = 324) of 343 individuals from 56 studies [ 8 , 11 , 12 , 14 16 , 19 21 , ...…”
Section: The Syndromic Phenotype Of Mecp2 Duplicat...mentioning
confidence: 99%
“…Developmental/psychomotor delay has been reported in most (n = 324) of 343 individuals from 56 studies [ 8 , 11 , 12 , 14 16 , 19 21 , 23 27 , 29 , 31 33 , 35 39 , 41 44 , 46 48 , 51 55 , 57 , 59 61 , 63 , 64 , 66 – 70 , 72 – 77 , 79 , 82 , 84 , 86 ], leading to moderate to severe intellectual disability (280 of 286 individuals from 57 studies [ 1 , 2 , 4 , 7 9 , 11 23 , 25 35 , 37 40 , 42 , 43 , 46 48 , 52 56 , 59 , 64 , 68 71 , 73 , 75 , 80 , 83 85 ]). Most children have impaired communication skills, as more than two-thirds (n = 179) of 261 individuals from 46 studies [ 2 , 3 , 5 , 7 , 9 , 11 , 13 , …”
Section: The Syndromic Phenotype Of Mecp2 Duplicat...mentioning
confidence: 99%